Development of a Fast Cake Ordering Mobile Application to Facilitate Cake Ordering for Customers at Cake Shops - Ninik Rahayu Ashadi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The purpose of this study is to determine the results of developing a Fast Cake Ordering mobile application to facilitate cake ordering for MSMEs in cake shops. This study uses the Research and Development (RD) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques include observation, instruments, and documentation. Data analysis techniques use feasibility analysis and user response analysis. The results of the study show that the Fast Cake Ordering mobile application was successfully developed through the stages of the model. This application is equipped with main features such as a product catalog, ordering, payment, and order tracking, and is considered feasible for use based on the analyzed data, obtaining an average feasibility score of 4.4 (very good category). The Fast Cake Ordering mobile application was successfully developed through the ADDIE model stages (Analysis, Design, Development, Implementation, Evaluation). The resulting application has key features such as product catalogs, ordering, payment, and order tracking that can be used by customers and MSME business owners. The developed application was declared suitable for use, with feasibility test results obtaining an average score of 4.52, which falls into the very good category. This indicates that the application fulfills aspects of ease of use, interface design, feature completeness, system speed, and user benefits. The research instruments used were proven valid and reliable, as shown by the validity test results where all items had an r-count value greater than the r-table value, and the reliability test results with a Cronbach’s Alpha value of 0.88, which is categorized as very high.